1994
DOI: 10.1109/10.324531
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a dipolar source in a skull phantom: realistic versus spherical model

Abstract: The dependence of the neuromagnetic source localization accuracy on the volume conductor model was studied by the analysis of measured magnetic fields generated by tangentially oriented dipoles in a realistically shaped skull phantom. When using a homogeneous sphere model in the localization procedure, the errors were found to increase from about 3 mm to about 9 mm when the distance between the dipoles and the inner surface of the skull increased from 1 cm to 3 cm, whereas when using a true, realistic model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 7 publications
1
17
0
1
Order By: Relevance
“…This model is certainly a considerable simplification of the true situation. The effect of an inappropriate volume conductor model can be assessed from Menninghaus et al [1994]. Since the estimated sources were located relatively superficially, the error made by choosing a homogeneous sphere as the volume conductor is presumably not greater than a few millimeters, and it can be assumed that all estimated source locations are effected in basically the same systematic way.…”
Section: General Methodological Considerationsmentioning
confidence: 99%
“…This model is certainly a considerable simplification of the true situation. The effect of an inappropriate volume conductor model can be assessed from Menninghaus et al [1994]. Since the estimated sources were located relatively superficially, the error made by choosing a homogeneous sphere as the volume conductor is presumably not greater than a few millimeters, and it can be assumed that all estimated source locations are effected in basically the same systematic way.…”
Section: General Methodological Considerationsmentioning
confidence: 99%
“…This strategy has a drawback, however, because the accuracy of the numerical computation is directly dependent on the mesh density, as has been evaluated using the boundary element method [Fuchs et al, 1998;Menninghaus et al, 1994;Roth et al, 1993;Yvert et al, 1995Yvert et al, , 1996Zanow and Peters, 1995;] or the finite element method . Fletcher et al [1995] have proposed a variant formulation of the BEM using the reciprocity theorem to increase the speed of realistic models in EEG, which cannot be as efficiently used in MEG.…”
Section: Introductionmentioning
confidence: 99%
“…Phantom studies have reported localization accuracy for EEG of 7-8 mm [Leahy et al, 1998] and for MEG of 2-4 mm [Gharib et al, 1995;Leahy et al, 1998;Menninghaus et al, 1994]. The localization superiority of MEG over EEG is less obvious in data from measurements made in patients.…”
Section: Introductionmentioning
confidence: 99%